Selected factors influencing impact of agriculture land development programme on Orang Asli community in Pahang, Malaysia - Hamid, Halilah (2012)
The main objective of this study was to identify the selected factors influencing impact of Agriculture Land Development Programme (ALDP) on Orang Asli community in Pahang, Malaysia. The impact dimensions are skills relate to oil palm plantations and farm practices, changes in lifestyle, ownership and economic related aspects to Orang Asli in Pahang. The factors such as demographic profile, level of perception of Orang Asli towards ALDP and level of participation of Orang Asli in ALDP management identified. This study also covers on problems and needs of community involved in ALDP. Finally, the study objective is to determine the relationship between selected independent variables and the impact of ALDP.